Carbohydrate and carbohydrate + protein for cycling time-trial performance - Osterberg, K. L.; Zachwieja, J. J.; Smith, J. W. (Journal of Sports Sciences, 2008)
Carbohydrate intake during endurance exercise delays the onset of fatigue and improves performance. Two recent cycling studies have reported increased time to exhaustion when protein is ingested together with carbohydrate. The purpose of the present study was to test the hypothesis that ingestion of a carbohydrate + protein beverage will lead to significant improvements in cycling time-trial performance relative to placebo and carbohydrate alone. Thirteen cyclists completed 120 min of constant-load ergometer cycling. Thereafter, participants performed a time-trial in which they completed a set amount of work (7 kJ/ kg) as quickly as possible. Participants completed four experimental trials, the first for familiarization and then three randomized, double-blind treatments consisting of a placebo, carbohydrate, and carbohydrate + protein. Participants received 250 ml of beverage every 15 min during the constant-load ride. Results: Time-trial performance for carbohydrate (37.1 min, s = 3.8) was significantly (P < 0.05) faster than placebo (39.7 min, s = 4.6). Time-trial performance for carbohydrate + protein (38.8 min, s = 5.5) was not significantly different from either placebo or carbohydrate. Ingestion of a carbohydrate beverage during two hours of constant-load cycling significantly enhanced subsequent time-trial performance compared with placebo. The carbohydrate + protein beverage provided no additional performance benefit.